TB screening, prevention and treatment cascade in a Malawi prison - Mangochi, P; Bossard, C; Catacutan, C; Van Laeken, D; Kwitonda, C; Ortuno, R; Chiwaula, L; Meis, M; Abura, A; Furin, J; Mpunga, J; Goemare, E; et al. (The international journal of tuberculosis and lung disease, 2022)
BACKGROUND Incarcerated individuals, especially in high HIV and TB burden settings, are at increased risk of latent TB infection and/or TB disease. We implemented a comprehensive HIV-TB intervention in a Malawi prison and studied its feasibility.METHODS Between February and December 2019, consenting individuals underwent screening for HIV, TB infection and TB disease. HIV-positive individuals without TB disease were treated with a fixed-dose combination of isoniazid, cotrimoxazole and vitamin B6 (INH-CTX-B6). HIV-negative persons with TB infection received 12 weeks of isoniazid and rifapentine (3HP).RESULTS Of 1,546 consenting individuals, 1,498 (96.9%) were screened and 1,427 (92.3%) included in the analysis: 96.4% were male, the median age was 31 years (IQR 25-38). Twenty-nine (2.1%) participants were diagnosed with TB disease, of whom 89.7% started and 61.5% completed TB treatment. Of the 1,427 included, 341 (23.9%) were HIV-positive, of whom 98.5% on antiretroviral therapy and 95% were started on INH-CTX-B6. Among 1,086 HIV-negative participants, 1,015 (93.5%) underwent the tuberculin skin test (TST), 670 (65.9%) were TST-positive, 666 (99.4%) started 3HP and 570 (85.5%) completed 3HP treatment.CONCLUSION A comprehensive TB screening and treatment package among incarcerated individuals was acceptable and feasible, and showed high prevalence of HIV, TB disease and TB infection. Treatment uptake was excellent, but treatment completion needs to be improved. Greater investment in comprehensive HIV-TB services, including access to shorter TB regimens and follow-up upon release, is needed for incarcerated individuals.BACKGROUND Incarcerated individuals, especially in high HIV and TB burden settings, are at increased risk of latent TB infection and/or TB disease. We implemented a comprehensive HIV-TB intervention in a Malawi prison and studied its feasibility.METHODS Between February and December 2019, consenting individuals underwent screening for HIV, TB infection and TB disease. HIV-positive individuals without TB disease were treated with a fixed-dose combination of isoniazid, cotrimoxazole and vitamin B6 (INH-CTX-B6). HIV-negative persons with TB infection received 12 weeks of isoniazid and rifapentine (3HP).RESULTS Of 1,546 consenting individuals, 1,498 (96.9%) were screened and 1,427 (92.3%) included in the analysis: 96.4% were male, the median age was 31 years (IQR 25-38). Twenty-nine (2.1%) participants were diagnosed with TB disease, of whom 89.7% started and 61.5% completed TB treatment. Of the 1,427 included, 341 (23.9%) were HIV-positive, of whom 98.5% on antiretroviral therapy and 95% were started on INH-CTX-B6. Among 1,086 HIV-negative participants, 1,015 (93.5%) underwent the tuberculin skin test (TST), 670 (65.9%) were TST-positive, 666 (99.4%) started 3HP and 570 (85.5%) completed 3HP treatment.CONCLUSION A comprehensive TB screening and treatment package among incarcerated individuals was acceptable and feasible, and showed high prevalence of HIV, TB disease and TB infection. Treatment uptake was excellent, but treatment completion needs to be improved. Greater investment in comprehensive HIV-TB services, including access to shorter TB regimens and follow-up upon release, is needed for incarcerated individuals.